COMPARISON OF THE ANIES AND GEMOY URGENT CAMPAIGN MODELS IN THE 2024 PRESIDENTIAL AND VICE PRESIDENTIAL ELECTIONS - Malindir, Gaston; Jamaludin, Hamzah; Prayitno, Adi (Universitas Negeri Semarang, 2024)
Entering the campaign period on January 21, each pair of candidates used various unique campaign models which were considered effective in attracting the hearts of the Indonesian people. Since the start, the public has been excited about Gemoy, which is the trending campaign model of candidate pair number 02 Prabowo-Gibran, while pair 01 Anies-Muhaimin has also attracted attention with the latest campaign model introduced by Desak Anies. This research uses a descriptive method with a qualitative approach. Data collection techniques in this research include literature study and field study. The research results show that there are significant similarities and differences between the Desak Anies and Gemoy campaign models. The similarity between the two lies in the target of the campaign model used, namely the young generation in the age range of 17-40 years with a percentage of 53% of the number of voters in Indonesia. On the other hand, the fundamental difference between the two lies in the ideas put forward in Desak Anies and Gimik which are put forward through the Gemoy campaign model. Specifically, the differences between these two campaign models can be seen using eight comparative variables referring to Nowak and Warneryd's Campaign Model theory which includes; Intended effect, Competing communication, Communication object, Target population & receiving group, Channel, The message, The communicator/sender, and The obtained effect. Despite this, the results in the field show that the majority of people tend to be interested in the Gemoy campaign model compared to the Desak Anies campaign model which tends to be intellectual, characterized by a debate of ideas.